The Effect of Temulawak (Shu Gu Jiang Huang) Administration on Stomach Pain in Patients with Stomach Heat Syndrome at LKP Daun Mas - Marjati Tjuatja; Muslihatin Khuril R; Aryaprana Nando; La Ode Muhammad Anwar (CV. AFDIFAL MAJU BERKAH, 2025)
Background: Gastric disorders with stomach heat syndrome are common digestive complaints encountered in clinical practice (World Gastroenterology Organization, 2021). Temulawak (Curcuma xanthorrhiza Roxb) contains active compounds such as curcuminoids, xanthorrhizol, and sesquiterpenes, which possess anti-inflammatory, gastroprotective, antimicrobial, and analgesic properties (Ariyani et al., 2020; Riswanti et al., 2021). Methods: This study aimed to determine the effect of Temulawak (Shu Gu Jiang Huang) on gastric pain with stomach heat syndrome. A pre-experimental one- group pre-test post-test design (Sugiyono, 2021) was employed. Thirty patients at LKP Daun Mas were selected using simple random sampling (Sugiyono, 2020). Pain intensity was measured using the Visual Analogue Scale (VAS) (Notoatmodjo, 2020) before and after the intervention. Data were analyzed using the Wilcoxon test. Results: The results showed a significant reduction in pain (p = 0.000), from a majority of moderate pain cases before the intervention (63.3%) to mild pain after the intervention (93.3%). The findings indicate that Shu Gu Jiang Huang is effective in reducing gastric pain associated with stomach heat syndrome. Conclusion: Shu Gu Jiang Huang demonstrates significant effectiveness in alleviating gastric pain in patients with stomach heat syndrome, supporting its use as part of integrative therapy in Traditional Chinese Medicine.